2012
DOI: 10.1002/mrd.22078
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling in mammalian egg activation and embryo development: The influence of subcellular localization

Abstract: Calcium (Ca2+) signals drive the fundamental events surrounding fertilization and the activation of development in all species examined to date. Initial studies of Ca2+ signaling at fertilization in marine animals were tightly linked to new discoveries of bioluminescent proteins and their use as fluorescent Ca2+ sensors. Since that time, there has been rapid progress in our understanding of the key functions for Ca2+ in many cell types and the impact of cellular localization on Ca2+ signaling pathways. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 138 publications
4
63
0
Order By: Relevance
“…Intracellular Ca 2C is an Prokineticin receptor genes and recurrent miscarriage important second messenger, and the downstream effects of calcium mobilization are likely to be numerous and may include activation of various secretory and signaling pathways (Petit & Bélisle 1995, Karl et al 1997, Tinel et al 2000. Ca 2C is closely moderated cell migration and invasion via Ca 2C -dependant effectors, such as calcineurin, calmodulin, actin, myosin, and integrins (Prevarskaya et al 2011), and also critical in mediating egg activation and successful preimplantation embryo development (Miao & Williams 2012). EG-VEGF and PKRs were reported to exert their biological functions by phosphorylation of their downstream target ERK1/2, through cross talk with the EGFR system (Evans et al 2008), or by activation of the PI3 kinase/Akt pathway (Lin et al 2002) and calcium/cAMP mobilization (Brouillet et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Ca 2C is an Prokineticin receptor genes and recurrent miscarriage important second messenger, and the downstream effects of calcium mobilization are likely to be numerous and may include activation of various secretory and signaling pathways (Petit & Bélisle 1995, Karl et al 1997, Tinel et al 2000. Ca 2C is closely moderated cell migration and invasion via Ca 2C -dependant effectors, such as calcineurin, calmodulin, actin, myosin, and integrins (Prevarskaya et al 2011), and also critical in mediating egg activation and successful preimplantation embryo development (Miao & Williams 2012). EG-VEGF and PKRs were reported to exert their biological functions by phosphorylation of their downstream target ERK1/2, through cross talk with the EGFR system (Evans et al 2008), or by activation of the PI3 kinase/Akt pathway (Lin et al 2002) and calcium/cAMP mobilization (Brouillet et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, mitochondria seemed to take part in the control of calcium homeostasis, working in coordination with the ER as a buffer of cytosolic Ca 2ϩ (45,46). It has already been shown that elevated [Ca 2ϩ ] in the mitochondrial matrix raises ATP production through different mechanisms (45,47,48) that include stimulation of substrate uptake (49) and TCA cycle (50), as well as direct priming of F 0 /F 1 -ATP synthase (51).…”
Section: Darkmentioning
confidence: 99%
“…Transient shifts in the concentration of cytoplasmic free Ca 2+ direct several key events at the commencement of mammalian embryonic development. The partitioning and redistribution of Ca 2+ among intracellular compartments contributes to a variety of mechanisms during fertilization and embryogenesis that control gene expression, mitochondrial activity, motility, secretion and protein trafficking, as detailed in a recent review (Miao and Williams 2012).…”
Section: Cellular Regulation Of Cytoplasmic Ca 2+ Concentrationsmentioning
confidence: 99%